Creative Urban Public Spaces as Sites of Informal Learning: A Mind Mapping Approach - Molostvova (Fainshtein), Elizaveta; Chkoniya, Valentina (European Journal of Social Science Education and Research, 2026)
This paper develops a conceptual and analytical model for understanding visitor attitudes toward public space as a process of social perception and meaning-making. Using semantic analysis and mind mapping techniques, the study examines Sevkabel Port, a regenerated waterfront public space, as a site of informal social interaction and experiential learning. Drawing on qualitative data from open-ended survey responses collected in August 2024 (N = 283), the research identifies dominant semantic clusters through which visitors articulate their perceptions and experiences. The analysis reveals five interrelated dimensions shaping visitor attitudes: infrastructure, activities, accessibility, social interaction, and mental imagery. These dimensions are integrated into a mind map that represents the cognitive and affective structure of how individuals interpret and engage with public space. While infrastructure and activity-related themes accounted for the largest share of references, mental imagery, such as atmosphere, visual openness, and proximity to water, played a central integrative role, connecting functional and social perceptions. The findings demonstrate that visitor attitudes emerge from the interaction of multiple perception dimensions rather than isolated spatial attributes, highlighting public space as a socially constructed environment embedded with symbolic and collective meanings. The proposed model offers a transferable analytical framework for examining how public spaces support informal learning, social interaction, and civic experience in hybrid cultural and leisure environments. By foregrounding visitor discourse, the study contributes to social science research on public space education and supports more inclusive, socially responsive approaches to urban design and policy.
Keywords: semantic analysis, mind mapping, visitor attitudes, place meaning, public spaces perception, experiential value, experiential learning